Epidemiology and Risk Factors for Cryptosporidiosis in Children From 8 Low-income Sites: Results From the MAL-ED Study. (26th April 2018) - Korpe, Poonum S; Valencia, Cristian; Haque, Rashidul; Mahfuz, Mustafa; McGrath, Monica; Houpt, Eric; Kosek, Margaret; McCormick, Benjamin J J; Penataro Yori, Pablo; Babji, Sudhir; Kang, Gagandeep; Lang, Dennis; et al.
Abstract : In this longitudinal multicenter study, 65% of children experienced Cryptosporidium infection during the first 2 years of life. Cryptosporidium was associated with severe diarrhea and dehydration and, in 2 South Asian sites, with stunted growth at age 2 years. Abstract: Background: Cryptosporidium species are enteric protozoa that cause significant morbidity and mortality in children worldwide. We characterized the epidemiology of Cryptosporidium in children from 8 resource-limited sites in Africa, Asia, and South America. Methods: Children were enrolled within 17 days of birth and followed twice weekly for 24 months. Diarrheal and monthly surveillance stool samples were tested for Cryptosporidium by enzyme-linked immunosorbent assay. Socioeconomic data were collected by survey, and anthropometry was measured monthly. Results: Sixty-five percent (962/1486) of children had a Cryptosporidium infection and 54% (802/1486) had at least 1 Cryptosporidium -associated diarrheal episode. Cryptosporidium diarrhea was more likely to be associated with dehydration (16.5% vs 8.3%, P < .01). Rates of Cryptosporidium diarrhea were highest in the Peru (10.9%) and Pakistan (9.2%) sites. In multivariable regression analysis, overcrowding at home was a significant risk factor for infection in the Bangladesh site (odds ratio, 2.3 [95% confidence interval CI, 1.2–4.6]). Multiple linear regression demonstrated a decreased length-for-age z score at 24 months in Cryptosporidium -positive children in the India (β = –.26 [95% CI, –.51 to –.01]) and Bangladesh (β = –.20 [95% CI, –.44 to .05]) sites. Conclusions: This multicountry cohort study confirmed the association of Cryptosporidium infection with stunting in 2 South Asian sites, highlighting the significance of cryptosporidiosis as a risk factor for poor growth. We observed that the rate, age of onset, and number of repeat infections varied per site; future interventions should be targeted per region to maximize success.